2023
DOI: 10.1038/s41396-023-01368-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative susceptibility of SARS-CoV-2, SARS-CoV, and MERS-CoV across mammals

Abstract: Exploring wild reservoirs of pathogenic viruses is critical for their long-term control and for predicting future pandemic scenarios. Here, a comparative in vitro infection analysis was first performed on 83 cell cultures derived from 55 mammalian species using pseudotyped viruses bearing S proteins from SARS-CoV-2, SARS-CoV, and MERS-CoV. Cell cultures from Thomas’s horseshoe bats, king horseshoe bats, green monkeys, and ferrets were found to be highly susceptible to SARS-CoV-2, SARS-CoV, and MERS-CoV pseudot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 103 publications
1
6
0
Order By: Relevance
“…Assessing the susceptibility of various bat species to the new coronavirus is the first step in the traceability process for bats, which can significantly reduce the challenges in tracing the new coronavirus. Paguma larvata, which showed inconsistency on LCAS, was not entirely consistent in the predictions, but recent studies have shown that it can be infected with the new coronavirus in vitro [ 18 ], which may be related to other factors inherent in the animal. Therefore, further research and analysis is needed on whether civet cats can be naturally infected and spread the new coronavirus.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Assessing the susceptibility of various bat species to the new coronavirus is the first step in the traceability process for bats, which can significantly reduce the challenges in tracing the new coronavirus. Paguma larvata, which showed inconsistency on LCAS, was not entirely consistent in the predictions, but recent studies have shown that it can be infected with the new coronavirus in vitro [ 18 ], which may be related to other factors inherent in the animal. Therefore, further research and analysis is needed on whether civet cats can be naturally infected and spread the new coronavirus.…”
Section: Discussionmentioning
confidence: 96%
“…However, animals at high risk of contracting SARS-CoV-2 cannot be accurately predicted by phylogenetic relationships based on comparisons of the entire ACE2 gene [ 15 , 17 ]. In-Vivo experiments animal infection provide the best opportunity to understand the susceptibility of SARS-CoV-2 across mammals [ 18 ]. However, conducting In-Vivo studies on a wide array of animals, particularly wildlife, presents a considerable complexity demanding increased manpower and resources.…”
Section: Introductionmentioning
confidence: 99%
“…The common raccoon dog was the most abundantly detected animal species in market wildlife stalls sampled on January 12 th , and in the wildlife stall with the most SARS-CoV-2 positive samples ( Figure 3A; Supplementary Table S15 ). The experimental susceptibility of civets is unknown, but Paguma larvata cells are susceptible to pseudotyped VSVs expressing the SARS-CoV-2 Spike protein in vitro (Li et al 2023). However, the susceptibility of bamboo rats, Malayan porcupines, and Amur hedgehogs remains unknown, and these species should also be prioritized for susceptibility testing.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the way we treated primates did not quanti ably affect the identi cation of hotpots of host richness, as major hotspots located in Southeast Asia, subequatorial Africa, and tropical South America remained the same. It is worth mentioning that there is molecular evidence that apes and monkeys of Africa and Asia could be susceptible to SARS-CoV-2 infection (Li et al, 2023), opening the possibility that some primate species could also play a role in betacoronavirus maintenance.…”
Section: Considerations On Framework Methodology and Validationmentioning
confidence: 99%